Long noncoding RNA RP11‐547D24.1 regulates proliferation and migration in papillary thyroid carcinoma: Identification and validation of a novel long noncoding RNA through integrated analysis of TCGA database. (1st May 2019) - Guo, Kai; Chen, Lili; Wang, Yunjun; Qian, Kai; Zheng, Xiaoke; Sun, Wenyu; Sun, Tuanqi; Wu, Yi; Wang, Zhuoying
Abstract: Long noncoding RNAs (lncRNAs) are known to be key regulators of numerous biological processes, and substantial evidence supports that abnormal lncRNA expression plays a significant role in tumorigenesis and tumor progression. However, the mechanism by which lncRNAs function in thyroid carcinoma are still unclear. To investigate the role of lncRNAs in the tumorigenesis of papillary thyroid carcinoma (PTC), we analyzed lncRNA data in The Cancer Genome Atlas RNA‐Seq database. A comparison of lncRNAs in cancerous thyroid tissues and normal tissues revealed hundreds of differentially expressed lncRNAs. Of 7589 lncRNAs identified in 561 thyroid cancer cases (503 cancerous tissues and 58 normal tissues), the expression levels of 144 were found to be aberrant (|log2 fold change| >2 and adjusted P  < 0.05). The top 10 lncRNAs with the most significant differences were LINC01977, RP11‐363E7.4, RP3‐483K16.4, RP11‐547D24.1, RUNDC3A‐AS1, AC093609.1, CTD‐2008L17.2, HAGLROS, UNC5B‐AS1, and LINC01354. In addition, CTD‐2008L17.2, HAGLROS, AC093609.1, UNC5B‐AS1, and RUNDC3A‐AS1 were shown to play vital roles in determining the histological cancer type. Furthermore, RP11‐547D24.1 and UNC5B‐AS1 could distinguish patients with different stages of PTC. The lncRNA RP11‐547D24.1 was validated by loss‐of‐function assays, revealing that downregulation of this lncRNA regulates thyroid tumor cell proliferation and apoptosis, invasion, and migration. This study demonstrates the potential for using lncRNAs to interpret the pathogenesis and development of PTC. Abstract : Effect of RP11‐547D24.1 on papillary thyroid carcinoma cell cycle, apoptosis, migration, and proliferation; RP11‐547D24.1 negatively regulates expression of tumor suppressor proteins (eg, PAX8/PPARG) in vitro.